The schoolbook and its influence on the training of the students of the basic education of public schools (Research, Society and Development, 2019)
The role that the textbook plays on teaching and learning in basic education students is very intense and notorious. Due to this influence of this didactic material on our Young people, it becomes urgent to verify the importance they cause in the formation of the students, since the book as a commodity and reproducer of discursive ideologies reinforce stereotypes and the denial of cultures and the exacerbation of others. This trend of appreciation of the hegemonic culture can be seen mainly through the books of geography. The teacher should use the textbook as another teaching aid, always trying to diversify the didactic materials, valuing the books that work the local aspects of each municipality, since books with situations closer to the students, strengthen local identities, thus identifying with the place and thus awakening sensations and feelings of familiarity. The teacher of geography as a facilitator of learning in the teaching-learning process plays a fundamental role, since he is the one who ultimately chooses the book that will work in the public school classrooms. Critical students and questioners of reality can only promote political action if they are stimulated to awaken the questioning side through their student training and the textbook is part of a larger composition in the formation of the students.